Research on Ship Energy Consumption Monitoring System Based on Computer Intelligent Technology. Issue 2 (October 2020) - Li, Fangxuan
Abstract: With the continuous development of automation technology, and has been widely used in all walks of life, the degree of automation integration in shipbuilding industry has also been greatly improved. In order to ensure the safe and reliable operation of marine power equipment, provide reliable and accurate real-time information for the operation of management personnel, and reduce human error judgment and great waste of manpower, a marine engine room monitoring system based on CAN bus is designed. The system uses computer intelligence technology to improve the real-time detection ability of ship power equipment parameters, and can display the important operation parameters and status of the equipment in real time. [1] When a fault is detected in the running state of the equipment, the system will automatically alarm and record the fault and adjust the operating parameters of the equipment to realize the control of the remote equipment.